Linear RAG scanning mediates editing of Igκ variable region repertoires - Xiang Li; Hongli Hu; Yiwen Zhang; Tammie Zhu; Ying Guan; Kai Xu; Xin Lin; Camille Hebert; Himanshu Batra; Jenny Zhou; Zhaoqing Ba; Duane R. Wesemann; et al. (Nature, 2026)
Abstract V(D)J recombination-mediated Igκ light chain variable region exon assembly in precursor (pre)-B cells involves recombination activating gene (RAG) endonuclease-orchestrated cleavage between and joining of paired Vκ and Jκ gene segments and flanking RAG-targeting recombination signal sequences (RSSs) 1–3 . The 3.1-megabase Igk contains 4 Jκs (Jκ1, 2, 4, 5) and 100-plus Vκs in clusters oriented for deletional or inversional joining 2 . Vκ-to-Jκ joining is ordered, with primary Vκ-to-Jκ1 rearrangements occurring first, followed by secondary rearrangements of upstream Vκs that replace primary VκJκ1s by joining to Jκ2-5 (refs. 4,5 ). Loop extrusion moves deletional-oriented and inversional-oriented, locus-wide Vκs past the Cer/Sis CTCF-binding element-based diffusion platform for short-range diffusional presentation to Jκ1-bound RAG in the primary recombination centre (RC). To achieve diffusion-mediated Vκ-to-Jκ1 joining, Igk evolved powerful Vκ-associated and Jκ-associated RSSs 3 . Secondary Igk rearrangements replace non-functional or autoreactive primary VκJκ1 rearrangements, expanding the Igκ repertoire and mediating central tolerance by means of receptor editing 4,6–11 . Here we describe studies that elucidate the physiologically critical secondary Igk recombination mechanism. Primary deletional and inversional VκJκ1 joins, respectively, delete or displace Cer/Sis, creating a pre-B cell population that harbours secondary VκJκ1-based RCs across the Vκ locus and leaves most unrearranged Vκs immediately upstream of secondary RCs in deletional orientation. High-throughput assays demonstrated that RAG scanning from secondary VκJκ1-based RCs, collectively, extends linearly across the Vκ locus in primary pre-B cell populations. Correspondingly, studies of induced pluripotent stem (iPS) cell-generated mouse models or cell lines with physiological VκJκ-rearrangements further revealed that deletional and, originally, inversional Vκs are mostly captured by Jκ2-5-based secondary RCs in deletional orientation by means of linear RAG scanning. Strong Vκ - RSSs contribute to restricting secondary rearrangements, including potential editing rearrangements, to Vκs immediately upstream of a given secondary RC and support, at a lower level, linear scanning-based inversional Vκ-to-Jκ rearrangements. Our findings implicate Cer/Sis deletion and/or displacement as a developmental switch that converts the two-loop-based diffusional primary Igk rearrangement mechanism into a one-loop-based linear scanning secondary rearrangement mechanism.